SITEMATIKA DALIL DALAM PENETAPAN HUKUM ISLAM: (Suatu Analisis Menurut Pemikiran Ulama Ushul Fikih) - Syarbaini, Ahmad (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2023)
The object of discussion of ushul fiqh is discussed by ushul scholars with different systematics, according to the focus of attention of each individual. In general, the method of establishing the arguments for the syara' law can be known from the Prophet's dialogue with Mu'adz bin Jabal when he was sent to Yemen as a qadhi. In the process of establishing syara' law, the use of argument plays a very important role. In terms of origin, the argument is divided into two parts, first; arguments originating from revelation, and second; The argument comes from ra'yu (reasoning). All arguments by some scholars can be returned to only four arguments, namely: first; the Bible, second; Al-Sunnah, third; Ijma', and fourth; Al-Ra'yu.